2017
DOI: 10.1200/jco.2017.35.15_suppl.e21563
|View full text |Cite
|
Sign up to set email alerts
|

Association between health status and social integration/loneliness in survivors of adolescent and young adult (AYA) cancers.

Abstract: e21563 Background: AYA cancer survivors are at risk of various adverse health outcomes, but the relation between health status, social integration (i.e., social network and support) and loneliness is understudied. Methods: 102 AYA survivors (mean age = 25 years; diagnoses = leukemia 27%; lymphoma 24%; brain tumors 9%; solid tumors 41%) and 102 age-sex-matched controls were recruited from a community-based online panel. Participants reported social network information (e.g., contact frequency, resources for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The two do not just affect the psychosocial wellbeing of the children, but also affect the mental and physical well-being of the children. For instance, loneliness has been found to associate with frequent visits to a doctor, school drop-out, depression, suicidal ideation, low-selfesteem, social anxiety, eating disorder, and sleeping problems (Ergen and Çikrikci, 2018;Gerst-Emerson and Jayawardhana, 2015;Huang et al, 2017;Maes et al, 2017), all to some extent found in our study. Adolescents with cancer mainly experienced reduced social interaction due to treatment and social isolation resulting from the stigma they experienced which in turn induced loneliness which also triggered some biophysical issues mentioned above.…”
Section: Discussionsupporting
confidence: 66%
“…The two do not just affect the psychosocial wellbeing of the children, but also affect the mental and physical well-being of the children. For instance, loneliness has been found to associate with frequent visits to a doctor, school drop-out, depression, suicidal ideation, low-selfesteem, social anxiety, eating disorder, and sleeping problems (Ergen and Çikrikci, 2018;Gerst-Emerson and Jayawardhana, 2015;Huang et al, 2017;Maes et al, 2017), all to some extent found in our study. Adolescents with cancer mainly experienced reduced social interaction due to treatment and social isolation resulting from the stigma they experienced which in turn induced loneliness which also triggered some biophysical issues mentioned above.…”
Section: Discussionsupporting
confidence: 66%
“…Given the documented relationship between social support and psychosocial outcomes in AYA cancer survivors (Huang et al, 2017; Manne and Miller, 1998; Rait et al, 1992; von Essen et al, 2000), it is important to develop interventions to foster supportive relationships throughout the cancer trajectory. In particular, it is necessary to develop tools to foster peer relationships because spending time with peers emerged as an important source of support for AYAs, yet peers’ absence during treatment was the most prominent source of feeling unsupported among this sample.…”
Section: Discussionmentioning
confidence: 99%
“…Among a sample of adolescents with cancer, those who were depressed reported significantly worse relationships with family and others than those not depressed (von Essen et al, 2000). Similarly, in a sample of adolescent and young adult (AYA) survivors, loneliness was significantly related to lower physical functioning and higher adverse outcomes, such as depression, anxiety, fatigue, and pain (Huang et al, 2017). Conflict with mothers has been associated with distress among adolescents with cancer (Manne and Miller, 1998).…”
mentioning
confidence: 99%
“…Researchers have emphasized the role of social support in helping AYA cancer patients/survivors make such positive adjustments. 13 , 14 , 15 However, Korean AYAs may need more attention from researchers regarding social support in order to adjust better to cancer diagnoses. Korean AYAs with cancer have reported a higher prevalence of psychological distress than their American peers, due to their unique sociocultural characteristics.…”
Section: Introductionmentioning
confidence: 99%